Psychoeducation, motivational interviewing, cognitive remediation training, and/or social skills training in combination for psychosocial functioning of patients with schizophrenia spectrum disorders: A systematic review and meta-analysis of randomized controlled trials - Lu, Erin Yiqing; Cheng, Andy S. K.; Tsang, Hector W. H.; Chen, Juan; Leung, Samuel; Yip, Annie; Lin, Jessie Jingxia; Lam, Zoe Violet; Zhang, Wufang; Zhao, Miaomiao; Ma, Ning (Frontiers in Psychiatry, 2022)
Objectives Psychoeducation, motivational interviewing, cognitive remediation training, and social skills training have been found to be effective interventions for patients with schizophrenia spectrum disorders. However, their efficacy on psychosocial functioning when provided in combination remains unclear, compared with all types of control conditions. It would also be meaningful to explore the differences of efficacy in patients with first-episode psychosis (FEP) and those with longer term of illness. Methodology The present review followed the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Full-text English journal articles of randomized controlled trials published in the past decade in the databases of PubMed, CINAHL Complete, Embase, and PsycINFO were searched. Included studies were all randomized controlled trials (RCTs) with participants diagnosed with schizophrenia spectrum disorders. The included studies should test combined interventions with at least two components from: psychoeducation, motivational interviewing, cognitive remediation training, and social skills training and incorporate assessment of psychosocial functioning at least at baseline and post-intervention. Results Seven studies were included for systematic review, and six of them were eligible for meta-analysis. Five out of the seven studies reported effects on psychosocial functioning that favored combined interventions over any type of control condition. A significant pooled effect was derived from the six studies, SMD = 1.03, 95% CI [0.06, 2.00], Z = 2.09, p = 0.04, I2 = 96%. However, the pool effect became insignificant when synthesizing five of the studies with non-FEP patients as participants and four of the studies testing relative effects of combined interventions compared with stand-alone interventions/interventions with one less component. None of the included studies adopted motivational interviewing and only one of the studies worked with FEP patients. Conclusion Psychoeducation, cognitive remediation training, and social skills training in combination can effectively enhance psychosocial functioning of patients with schizophrenia spectrum disorders. It is warranted to conduct more RCTs to test the effects of different specific combinations of the above interventions on psychosocial functioning, especially in FEP patients.